Pertolongan Pertama Luka Gores Dalam Meningkatkan Pengetahuan Anak Usia Dini Di Tpq Ra.Ar-Rahman - Lalu Saparwadi; Moh. Juhad; Asdiati Wahidah; Juniar Lestiana; Laeli Rizki Amelia; Lia Handayani; Manun Astuti (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Young children are particularly vulnerable to minor injuries such as abrasions due to their high level of physical activity. A lack of understanding regarding initial wound care can increase the risk of infection. Therefore, a community service activity was conducted to provide education on first aid for abrasions in order to enhance the knowledge of early childhood children. This community service aimed to educate children on proper first aid treatment for minor wounds using a child-friendly approach. The activity took place at TPQ RA. Ar-Rahman, located in Dusun Lingkok Dudu, Labuan Haji Subdistrict, East Lombok Regency, and was carried out over the course of one day. A total of 60 children aged between 4 and 6 years, all in the pre-school stage, participated in the activity. The educational session employed lectures, question-and-answer interactions, and simulation methods. The program was implemented in three stages: the pre-implementation stage, the implementation stage, and the evaluation stage. The results of the activity indicated an improvement in the children's understanding and skills in dealing with minor injuries, as well as fostering a sense of self-care and health awareness from an early age.